EXPLORING THE DIVERSITY AND SPECIES COMPOSITION OF FERN (Pteridophyta) in SARAH, LEUPUNG, ACEH BESAR - Mahlil Yulian Winda; Meutia Zahara; Nurul Fajriana; Suwarniati Suwarniati (Jurnal Biologi Sains dan Kependidikan, 2024)
The research on the Composition and Diversity of Ferns (Pteridophyta) in the Sarah Area, Leupung Subdistrict, Aceh Besar Regency, was conducted in February 2020. The aim of this study was to identify the types of ferns found in the Sarah Leupung area and to determine their diversity index. The method used was an exploratory survey with direct observation at three stations. Data analysis was performed using the Shannon-Wiener Diversity Index formula. The results showed that there were 10 species with a total of 250 individual ferns, and the diversity index was categorized as moderate with H' = 2.053211.